Police–Government Collaboration in MSME Empowerment: Evidence from Bangka Belitung - Bahar Buasan; Vita Mayastinasari; Sari Wahyuni; Riani Rachmawati (Eduvest - Journal of Universal Studies, 2026)
This study discusses the economic growth paradox without security in the Bangka Belitung Islands Province, where reported crimes have increased by 37.6 (1,566 to 2,155 cases) over the period between 2021 to 2023, despite the 12.8 growth in MSMEs amid an economic transition not based on tin mining. The study dwells on the police-local government cooperation in the empowerment of MSMEs as a Crime Prevention Through Social Development (CPSD) measure. Using qualitative case study research approach and interviewing the stakeholders of ABCGM (Academy, Business, Community, Government, Military/Police) by using in-depth interviews and focus groups, this study develops the Community-Based Empowerment Model (Model BBM). The results illustrate the multidimensional aspect of MSMEs in security, which constitutes surveillance networks, economic stabilization, social capital formation, and situational crime prevention. The BBM Model works out Bhabinkamtibmas (community police officers) as ecosystem orchestrators in five functions: assessment, bridging, capacity-building, governance, and monitoring. The paper is an addition to the theoretical synthesis of procedural justice developed by Tyler, community policing developed by Bayley and economic criminology, as it provides a practical road map of the 17,000 Indonesian island communities shifting to extractive ones.